2020
DOI: 10.1155/2020/2685238
|View full text |Cite
|
Sign up to set email alerts
|

Game Modelling and Strategy Research on Trilateral Evolution for Coal-Mine Operational Safety Production System: A Simulation Approach

Abstract: In view of the particularity and high risk of coal mining industry, the decision-making behavior of multiple agents inside the coal-mine enterprise plays a very important role in ensuring the safety and sustainable development of coal mining industry. The existing literature studies on coal-mine safety production focus mainly on statically analyzing the game among the external entities such as the government, the enterprises themselves, and the employees inside the enterprise from a macro perspective,are short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Meng et al ( 75 ) reviewed relevant articles on game theory and safety management during 2010–2019 and affirmed that the application of game theory in safety management research is conducive to determine the causes and motivations of unsafe behaviors. Li et al ( 79 ) also discussed the use of evolutionary game theory to describe the interaction between stakeholders in China's coal mine safety production system, including organizations, front-line miners, and front-line managers. They found that when certain conditions are met, the decision-making behaviors of organizations, miners, and managers can evolve into a unique ideal steady state.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meng et al ( 75 ) reviewed relevant articles on game theory and safety management during 2010–2019 and affirmed that the application of game theory in safety management research is conducive to determine the causes and motivations of unsafe behaviors. Li et al ( 79 ) also discussed the use of evolutionary game theory to describe the interaction between stakeholders in China's coal mine safety production system, including organizations, front-line miners, and front-line managers. They found that when certain conditions are met, the decision-making behaviors of organizations, miners, and managers can evolve into a unique ideal steady state.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e effective supervision of coal miners' emotions is an important means to achieve coal mine safety [40]. When certain conditions are met, all parties in the game can reach the ideal stable state [41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The frequent occurrence of recent financial crises and the gradual development of their impact from regional to global are constant reminders of the need to strengthen risk management [5]. The core of risk management is risk measurement, and there is no risk management if the risk of financial assets cannot be accurately measured.…”
Section: Introductionmentioning
confidence: 99%